2019
DOI: 10.1186/s13045-019-0798-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in HER2-positive breast cancer: state of the art and future perspectives

Abstract: Breast cancer (BC) is a complex disease with primary or acquired incurability characteristics in a significant part of patients. Immunotherapeutical agents represent an emerging option for breast cancer treatment, including the human epidermal growth factor 2 positive (HER2+) subtype. The immune system holds the ability to spontaneously implement a defensive response against HER2+ BC cells through complex mechanisms which can be exploited to modulate this response for obtaining a clinical benefit. Initial immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 188 publications
(180 reference statements)
2
98
0
Order By: Relevance
“…Specifically, blocking immune evasion and attracting more TILs and fewer Tregs (reactivating immunogenicity of BC) to the tumor microenvironment can improve the OS of BC patients [19,23,[115][116][117][118][119]. Sixteen percent of HER2 + subtypes are lymphocyte predominant (> 50-60% of TILs present) and are associated with improved outcome (EFS: event-free survival, OS) with many treatment modalities [19,[120][121][122][123][124]. The FinHER trial demonstrated the link between improved response to trastuzumab and higher levels of TILs among HER2 + BC patients [125].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, blocking immune evasion and attracting more TILs and fewer Tregs (reactivating immunogenicity of BC) to the tumor microenvironment can improve the OS of BC patients [19,23,[115][116][117][118][119]. Sixteen percent of HER2 + subtypes are lymphocyte predominant (> 50-60% of TILs present) and are associated with improved outcome (EFS: event-free survival, OS) with many treatment modalities [19,[120][121][122][123][124]. The FinHER trial demonstrated the link between improved response to trastuzumab and higher levels of TILs among HER2 + BC patients [125].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
“…As per available literature, potential predictive biomarkers that can be used to select patients who may benefit from combined treatment using HER2-targeted and PD-1/PD-L1 axis based therapeutic agents are (1) HER2 amplification/overexpression, (2) PD-1/PD-L1 expression, (3) presence of a greater number of TILs and fewer Tregs, (4) higher TMB (tumor mutation burden), (5) PTEN expression, and (6) expression of CD5, CD74, CD96, and CD226, to name only few [38,86,121,[131][132][133][134][135][136][137][138]. However, it is still not clear which combination of clinicopathological factors are most reliable predictive biomarkers to implement effective treatment protocols using anti-HER2 and/or PD-1/PD-L1 pathways [39,139].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This is also caused by the possibility of endocrine hormone therapy as a treatment option. Luminal B type is de ned by the presence of estrogen and progesterone receptors with additionally a high proliferation rate compared to Luminal A. Her2-enriched type is de ned by the expression of the oncogene human epidermal growth factor receptor, which stimulates proliferation and inhibits apoptosis [48]. Importantly, it can be targeted by an antibody treatment, namely trastuzumab, which shows the utter importance of this receptor [48].…”
Section: Discussionmentioning
confidence: 99%
“…Luminal B type is de ned by the presence of estrogen and progesterone receptors with additionally a high proliferation rate compared to Luminal A. Her2-enriched type is de ned by the expression of the oncogene human epidermal growth factor receptor, which stimulates proliferation and inhibits apoptosis [48]. Importantly, it can be targeted by an antibody treatment, namely trastuzumab, which shows the utter importance of this receptor [48]. Lastly, the triple negative type is de ned by the absence of any of these receptors, resulting in the worst prognosis and limited treatment options [10].…”
Section: Discussionmentioning
confidence: 99%